Spatio-Temporal object relational for biodiversity system (STORe-Biodi) - Wahid, Mohd. Taib; Kamruzzaman, A. Z. M.; Mohamed Shariff, Abdul Rashid (International Journal of Computer Science and Network Security, 2006)
Spatio-temporal data model for biodiversity is 'owing importance to the biodiversity data anagement, forest and environment control. Datio-temporaldata models have received much tention in the database research community ~cause of their practical importance and teresting challenges they pose. This paper is scussed upon the research activities of 'lecting, designing, implementing the data odel. The paper can be divided by two major lrts, fIrst: discuss about biodiversity data model ld secondly: spatio-temporal conceptual amework design of biodiversity data model for ng terms stewardship of biodiversity formation. In this paper our main objective to inimize the extension required in SQL guage. This paper also focuses on the unifIed ode1s of space and time using object-relation ~proach.In particular, we propose a conceptual Dject-relational spatial temporal data model lsed on Donna J. Peuquet's pyramid framework. ndard and user management queries are ~pliedto test the model. After extensive testing, e data model performed admirably in anaging biodiversity data.